Camel meat perception and the factors influencing its consumption willingness among Algerian consumers - B. Hamad; L. Hadef; S. Amara (Теория и практика переработки мяса, 2025)
The purpose of this research was to evaluate Algerian consumers' perceptions of camel meat and identify the variables driving their intention to consume it. A survey of 142 participants selected at random through in-person interviews and a self-administered questionnaire in El Oued district located in the southeast of Algeria assisted in this study. The data revealed that 93.7% of the participants had consumed camel meat previously at least once; however, merely 6.3% of participants had never consumed this meat before. The majority of participants (83.1%) held a favorable perception of camel meat and expressed a willingness to consume it again (80.3%). Conversely, 59.2% of the participants said that eating camel meat was often linked with particular occasions, like religious and sociocultural activities. Taste (65.5%) was the primary factor influencing customers' choice of red meat varieties, while tenderness (58.5%) was the most strongly correlated attribute with camel meat perception. Analysis of the determinant variables showed that males were willing to eat camel meat at a higher rate than females (92.1% vs. 66.7%; χ2 = 14.440; p = 0.000). A substantial beneficial impact was also evident due to prior consumption and the favorable perception of this meat among consumers (χ2 = 29.043; p = 0.000 and χ2 = 52.857; p = 0.000). The willingness to indulge in camel meat consumption was also significantly impacted by ascertaining how frequently consumers consume this meat. Altogether, this investigation offers a clear understanding of how consumers perceive the quality of camel meat and the factors that influence its consumption.